Heme Oxygenase-1 Is a Pivotal Modulator of Bone Turnover and Remodeling: Molecular Implications for Prostate Cancer Bone Metastasis - Anselmino, Nicolás (2019)
Aims: Bone is the most frequent site of prostate cancer (PCa) metastasis. Tumor cells interact with the bone microenvironment interrupting tissue balance. Heme oxygenase-1 (HO-1; encoded by Hmox1) appears as a potential target in PCa maintaining the cellular homeostasis. Our hypothesis is that HO-1 is implicated in bone physiology and modulates the communication with PCa cells. Here we aimed at (i) assessing the physiological impact of Hmox1 gene knockout (KO) on bone metabolism in vivo and (ii) determining the alterations of the transcriptional landscape associated with tumorigenesis and bone remodeling in cells growing in coculture (PCa cells with primary mouse osteoblasts [PMOs] from BALB/c Hmox1+/+, Hmox1+/-, and Hmox1-/- mice). Results: Histomorphometric analysis of Hmox1-/- mice bones exhibited significantly decreased bone density with reduced remodeling parameters. A positive correlation between Hmox1 expression and Runx2, Col1a1, Csf1, and Opg genes was observed in PMOs. Flow cytometry studies revealed two populations of PMOs with different reactive oxygen species (ROS) levels. The high ROS population was increased in PMOs Hmox1+/- compared with Hmox1+/+, but was significantly reduced in PMOs Hmox1-/-, suggesting restrained ROS tolerance in KO cells. Gene expression was altered in PMOs upon coculture with PCa cells, showing a pro-osteoclastic profile. Moreover, HO-1 induction in PCa cells growing in coculture with PMOs resulted in a significant modulation of key bone markers such as PTHrP and OPG. Innovation and Conclusion: We here demonstrate the direct implications of HO-1 expression in bone remodeling and how it participates in the alterations in the communication between bone and prostate tumor cells.